Probably, Approximately Correct: Nature's Algorithms for Learning and Prospering in a Complex World - Leslie Valiant (Basic Books, 2013)
How does life prosper in a complex and erratic world? While we know that nature follows patterns Ã¢â,¬â€œ such as the law of gravity Ã¢â,¬â€œ our everyday lives are beyond what known science can predict. We nevertheless muddle through even in the absence of theories of how to act. But how do we do it? In Probably, Approximately Correct, computer scientist Leslie Valiant presents a masterful synthesis of learning and evolution to show how both individually and collectively we not only survive, but prosper in a world as complex as our own.The key is \\\probably approximately correct\\\ algorithms, a concept Valiant developed to explain how effective behavior can be learned. The model shows that pragmatically coping with a problem can provide a satisfactory solution in the absence of any theory of the problem. After all, finding a mate does not require a theory of mating. Valiant\\\'s theory reveals the shared computational nature of evolution and learning, and sheds light on perennial questions such as nature versus nurture and the limits of artificial intelligence.